2020
DOI: 10.3390/ani10101911
|View full text |Cite
|
Sign up to set email alerts
|

Managing Free-Range Laying Hens—Part B: Early Range Users Have More Pathology Findings at the End of Lay but Have a Significantly Higher Chance of Survival—An Indicative Study

Abstract: While free-range laying hens frequently experience health and welfare challenges, the contribution of range use towards these risks are largely unknown. The aim of this pilot study was to investigate the survival, health and welfare of commercial free-range laying hens and explore the association with early range use. Range use of 9375 Lohmann Brown hens housed within five flocks was assessed during 18–21 weeks of age and individual hens were classified as “rangers” (frequent range users), “roamers” (intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…(2016). Although range use differs considerably between individuals within a flock (Larsen et al., 2017; Sibanda et al., 2020), a very large percentage of hens go outside at least some of the time (> 95% according to (Hartcher et al., 2016; Campbell et al., 2017b; Larsen et al., 2017; Buijs et al., 2020)), but 71% in (Gebhardt‐Henrich et al., 2014). Birds that range more at the start of lay (relative to their flock mates) also range more when older (Rodriguez‐Aurrekoetxea and Estevez, 2016) (Chielo et al., 2016).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016). Although range use differs considerably between individuals within a flock (Larsen et al., 2017; Sibanda et al., 2020), a very large percentage of hens go outside at least some of the time (> 95% according to (Hartcher et al., 2016; Campbell et al., 2017b; Larsen et al., 2017; Buijs et al., 2020)), but 71% in (Gebhardt‐Henrich et al., 2014). Birds that range more at the start of lay (relative to their flock mates) also range more when older (Rodriguez‐Aurrekoetxea and Estevez, 2016) (Chielo et al., 2016).…”
Section: Assessmentmentioning
confidence: 99%
“…However, for keel bone fractures and fearfulness it is often difficult to determine if those are the cause or the effect of low use of the outdoor range. Individuals that spent more time outdoors when young (18–21 weeks) were: 2.4 times more likely to survive to the end of lay than hens that spent little time outdoors and had a lower occurrence of fatty liver syndrome (Sibanda et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…Range use is also associated with reduced risk of plumage damage and feather pecking (see the next welfare issue) (Bestman and Wagenaar 2003;Bestman et al 2017). All these issues combined may result, therefore, in low flock productivity and uniformity, as well as low animal welfare (Sibanda et al 2020a(Sibanda et al , 2020b(Sibanda et al , 2020c.…”
Section: Range Use In Broiler Chickens and Laying Hensmentioning
confidence: 99%
“…Studies have shown that hens kept with access to a run are less likely to peck feathers and have a better plumage condition [39,[60][61][62]. However, the benefits that hens derive from access to the run largely depend on whether the birds choose to use it or not.…”
Section: Discussionmentioning
confidence: 99%